(untitled) (Bangladesh Journal of Botany, 2023)
The change characteristics of 5 indicators of soil organic carbon (SOC) content, dehydrogenase activity, protease activity, catalase activity, and maize yield were analyzed at 0a before and 3, 4, and 8 years after remediation in the study area. Results showed that the coefficient of variation (CV) of each index in the study area was generally small, the variation degree of soil organic carbon content was the highest, and the variation degree of catalase activity and maize yield was the least. After the implementation of the gully land consolidation, the CV of each index in the gully showed a decreasing trend, and the distribution of each index in the gully tended to be uniform. With the increase of remediation years, SOC content, soil enzyme activity and maize first yield showed a trend of decrease and then increase, and the change trend of each index was slightly different at gully head, the middle of gully and the gully outlet, the change is significant. At the gully head, the SOC content did not return to the level of 0a after 8a of remediation, and the other indicators returned to the level of 0a or higher than that of 0a. At the gully head, at p < 0.05 level, maize yield showed a very significant positive correlation with catalase activity, and a negative correlation with protease activity. In the middle of gully, there was a significant positive correlation with organic carbon content, soil protease and catalase activities, and it was negatively correlated with dehydrogenase activity but not significantly. At the gully outlet, there was a very significant positive correlation with protease activity. Bangladesh J. Bot. 52(2): 459-466, 2023 (June) (Special)